2010
DOI: 10.1186/1471-2105-11-565
|View full text |Cite
|
Sign up to set email alerts
|

Reanalyze unassigned reads in Sanger based metagenomic data using conserved gene adjacency

Abstract: BackgroundInvestigation of metagenomes provides greater insight into uncultured microbial communities. The improvement in sequencing technology, which yields a large amount of sequence data, has led to major breakthroughs in the field. However, at present, taxonomic binning tools for metagenomes discard 30-40% of Sanger sequencing data due to the stringency of BLAST cut-offs. In an attempt to provide a comprehensive overview of metagenomic data, we re-analyzed the discarded metagenomes by using less stringent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
1
16
2
Order By: Relevance
“…Finally, we note that the method used in MetaDomain shares a similar rationale to the recent work by Weng et al 14 Weng et al reported that taxonomic binning tools for metagenomes discard 30-40% of Sanger sequencing data due to the stringency of BLAST cut-offs. Thus, they re-analyzed the discarded reads using less stringent cut-offs.…”
Section: Related Workmentioning
confidence: 53%
“…Finally, we note that the method used in MetaDomain shares a similar rationale to the recent work by Weng et al 14 Weng et al reported that taxonomic binning tools for metagenomes discard 30-40% of Sanger sequencing data due to the stringency of BLAST cut-offs. Thus, they re-analyzed the discarded reads using less stringent cut-offs.…”
Section: Related Workmentioning
confidence: 53%
“…The description of these methods here is a summary of the description available in [24]. We next describe a summarization algorithm that uses the UMLS concepts and relations to construct a graph-based representation for the document to be summarized.…”
Section: Methodsmentioning
confidence: 99%
“…Application of these new methods would lower the computational cost of the method. Similarity-based taxonomic classifications methods are not robust to horizontal gene transfer events and therefore alternative classification algorithms may be more suitable for contaminant detection than PathoScope (Kunin et al, 2008;Weng et al, 2010). Other methods such as MicrobeGPS and…”
Section: /18mentioning
confidence: 99%